Translation of preclinical ethnomedicine data in LMICs: the example of rooibos - Pretorius, Lesha; Smith, Carine (Frontiers in Pharmacology, 2023)
All disease, but especially non-communicable diseases, are related to dysfunction of one or more regulatory systems. In developing countries, long-term management of patients with chronic diseases has many challenges and is generally not financially viable, but Africa in particular, which is rich in diverse ethnomedicines presents a more feasible long-term therapeutic approach in this niche.However, despite comprehensive preclinical investigations on numerous plant-derived candidate medicines, only a small portion of these reach the patient as recognised medicines.In this review, we use the example of rooibos (Aspalathus linearis (Burm.f.) R.Dahlgren) -which is globally consumed as aromatic, caffeine-free tea -to illustrate the hurdles that need to be overcome in the low-to middle-income countries, before progression of ethnomedicines to official treatment regimens can be achieved.In terms of methodology, regulatory system focused rooibos papers indexed on PubMed for the past three decades (n=112) were accessed. Papers reporting duplication of previous results were excluded, as well as review papers.Topics covered includes the high standard of ethnomedicine drug discovery and efficacy testing research performed in Africa (and South Africa in particular in the case of rooibos), the potential bias in terms of preclinical research focus, ethnomedicine ownership and the requirement for independent clinical trial coordination and/or management.